IFC Annual Report 2008 : Creating Opportunity, Volume 2. IFC 2008 Financials, Projects, and Portfolio - International Finance Corporation (Washington, DC, 2012)
The International Finance Corporation (IFC) annual report continues an approach pioneered last year, combining information on the investments and advisory services, sustainability, development effectiveness, and donor partnerships. The report covers fiscal 2008 (July 1, 2007, through June 30, 2008) and discusses the year's new business as well as the performance and development results of the portfolio. In FY08, new investments totaled $16.2 billion, rising 34 percent from the previous year. The IFC seeks to enhance the accountability and to articulate the vision, core corporate values, purpose, and the way the IFC works for a wide range of stakeholders: client companies, governments, partners, local communities affected by the activities, advocacy organizations, investors, and the staff.